Vulnerability: Self-study’s contribution to social justice education - Corinne Knowles (Perspectives in Education, 2014)
Teaching, as a social justice project, seeks to undo and re-imagine oppressive pedagogies in order to transform teachers, their students, and the knowledge with which they work. In this article, I argue that self-study can contribute to social justice in a number of ways by, for instance, making the sometimes limiting norms that frame teaching and learning visible; inviting my own vulnerability through peer and student reflections and feedback, and noticing the important relationship between ontology and epistemology in teaching and learning. One means to avoid the narrow way in which self-study might apply to only one person’s practice is to use theory to legitimise it and make it more broadly applicable. In this study, I use Judith Butler’s ideas relating to vulnerability in order to explain the way in which my teaching and learning is framed and to show how normative frameworks that define teaching can be expanded to be more inclusive. I use excerpts of peer and student feedback in order to demonstrate how vulnerability, reconfigured, can lead to powerful new knowledge.